2015
DOI: 10.4103/0301-4738.176031
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular cytokines in retinal vein occlusion and its relation to the efficiency of anti-vascular endothelial growth factor therapy

Abstract: Purpose:To analyze the change in the concentration of intraocular cytokines (ICs) in patients with retinal vein occlusion (RVO) before and after intravitreal ranibizumab therapy (IVR), and to find the correlations of IC with clinical activity of RVO and efficiency of treatment.Materials and Methods:Forty-four patients aged 46–79 years old (mean age: 60.7 ± 7.5 years old) with RVO and macular edema (18 patients – with central RVO, 26 – with branch RVO) treated with IVR were included into the study. The concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
2
9
1
1
Order By: Relevance
“…В то же время у больных с мхНВ регистрирова-лось увеличение концентрации 9 ЦК -представи-телей практически всех эффекторных групп [16,17]. По сравнению с данными группы контроля практи-чески в 7 раз был увеличен тромбоцитарный фактор роста (PDGF -BB), один из основных проангио-генных факторов, играющий важную роль в ангио-генезе, который незаменим для процесса рекрути-рования, пролиферации и созревания перицитов, необходимых для стабилизации формирующейся сосудистой сети [1,18].…”
Section: результаты и обсуждениеunclassified
“…В то же время у больных с мхНВ регистрирова-лось увеличение концентрации 9 ЦК -представи-телей практически всех эффекторных групп [16,17]. По сравнению с данными группы контроля практи-чески в 7 раз был увеличен тромбоцитарный фактор роста (PDGF -BB), один из основных проангио-генных факторов, играющий важную роль в ангио-генезе, который незаменим для процесса рекрути-рования, пролиферации и созревания перицитов, необходимых для стабилизации формирующейся сосудистой сети [1,18].…”
Section: результаты и обсуждениеunclassified
“…Direct comparison between biomarker levels in controls and patients with macular oedema secondary to BRVO and CRVO was reported by Shchuko et al [22]. This group reported signi cantly higher levels of VEGF and pro-in ammatory cytokines and chemotaxins -IL-1β, IL-6, IL-8, IL-12, IL15, IFN-γ TNF-α, MCP-1 and RANTES in RVO patients as compared to control.…”
Section: Introductionmentioning
confidence: 68%
“…Surprisingly, they also reported statistically signi cant higher levels of anti-in ammatory markers like IL-4, IL-10, IL-13, IL-17 and RAIL-1 (Receptor antagonist interleukin-1). Therefore retinal activity was concluded to be a balance between pro-in ammatory and anti-in ammatory mechanisms [22]. They also noted that there was a signi cant reduction in VEGF levels following treatment with the anti-VEGF agent, Ranibizumab, in those patients who had a good clinical response.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports showing that response to anti-VEGF is associated with aqueous VEGF levels. 4 In addition, Shchuko et al 6 showed that eyes with CRVO and branch retinal vein occlusion with insufficient response to ranibizumab had high concentrations of a number of cytokines including VEGF, interleukin 8, monocyte chemoattractant protein-1, interleukin 10, and interleukin 13. In our study, eyes that persistently achieved a fluid-free status may have had intraocular VEGF levels that could be sufficiently suppressed by anti-VEGF therapy based on the LEAVO retreatment criteria.…”
Section: Discussionmentioning
confidence: 99%